1989
DOI: 10.1111/j.1346-8138.1989.tb01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Pustular Dermatosis of the Scalp Associated with Autoimmune Diseases

Abstract: A 36-year-old woman visited our hospital with a five month history of persistent pustulation, crusting, and alopecia on the vertex of the scalp. No pathological organisms were isolated from the lesions. Histological examination revealed non-specific changes of chronic inflammation with destroyed follicles. Antibiotic therapy produced no response, but steroid therapy was effective. From these observations, a diagnosis of erosive pustular dermatosis of the scalp (EPDS), as described by Pye et al., was made. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Moreover, autoimmune disorders have been described in association with EPDS. Therefore, it has been suggested that physical trauma to the skin might cause auto-antibodies production against skin structures, resulting in a secondary inflammatory reaction 8,9 . The fact that EPDS responds to topical antiinflammatory agents supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, autoimmune disorders have been described in association with EPDS. Therefore, it has been suggested that physical trauma to the skin might cause auto-antibodies production against skin structures, resulting in a secondary inflammatory reaction 8,9 . The fact that EPDS responds to topical antiinflammatory agents supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis remains unknown, but predisposing factors such as recent or past local trauma, skin grafting and excessive exposure to sunlight on the bald scalp [12] have been reported. Furthermore, auto-immune diseases have been described in association with EPDS such as rheumatoid arthritis [13], Hashimoto’s thyroiditis, auto-immune hepatitis and Takayasu’s aortitis [15], suggesting the possibility of a common immunological dysfunction. It can be supposed that physical damage to the skin could induce the production of auto-antibodies against epidermal and dermal structures with a secondary inflammatory reaction; furthermore, EPDS responsiveness to steroids and anti-inflammatory drugs may confirm this auto-immune hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…According to most authors, these organisms represent secondary colonization rather than primary infection without playing a role in the pathogenesis of EPDS as it is confirmed by unsuccessful results of all therapeutic attempts with antibacterial or antimycotic drugs. Laboratory data are usually normal even if sometimes elevated values of inflammation markers (erythrocyte sedimentation rate, C-reactive protein, polyclonal hypergammaglobulinaemia) and rarely the presence of various auto-antibodies (rheumatoid factor, thyroglobulin and microsomal antibodies, liver antibodies and so on) are described [2, 13, 14]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations